Biosférická rezervácia Poľana a jej rozšírenie v roku 2016 - Beňušková, Zuzana (Studia Etnologiczne i Antropologiczne, 2017)
The Pol’ana Biosphere Reserve is situated in Central Slovakia. In its southern part, in the scattered area, the town of Hriňová was built, and its districts became part of the biosphere reserve and the protected natural area. For the residents it means both benefits and disadvantages. This article analyzes the situation of 2016 when the Biosphere Reserve area was expanded under the UNESCO program.